STRUCTURAL AND CLINICAL FEATURES OF THE ORAL CAVITY IN WOMEN DURING THE POSTMENOPAUSAL PERIOD - Mamedov Izmir; Budaychiev Gasan Magomed-Alievich; Patimat Arsenovna Kurbanova (TADQIQOTLAR, 2026)
ANNOTATION The relevance of this study is determined by the growing proportion of postmenopausal women worldwide and the significant impact of hormonal changes on oral health. The decline in estrogen levels after menopause is associated with a wide range of alterations in the organs and tissues of the oral cavity, including reduced salivary secretion, mucosal atrophy, decreased bone mineral density, and an increased susceptibility to periodontal diseases and tooth loss. Despite the well-recognized systemic effects of menopause, oral manifestations remain insufficiently studied, particularly from a combined clinical and morphological perspective. Early detection of structural and functional changes in oral tissues is essential for the prevention, timely diagnosis, and effective management of dental diseases in this population. Furthermore, postmenopausal women often present with complex comorbid conditions, which may exacerbate oral pathologies and complicate treatment strategies. Therefore, a comprehensive clinical and morphological assessment of the oral cavity in this group is of high scientific and practical importance. The findings of this study will contribute to improving diagnostic approaches, optimizing preventive measures, and developing personalized treatment protocols, ultimately enhancing the quality of dental care and overall quality of life for postmenopausal women.